Hydrophobic Ti3C2Tx/PU sponge prepared from commercial amphiphilic PU sponge for oil/water separation with ultrahigh flux. Issue 6 (December 2022) - Li, Sai; Zhang, Lei; Qin, Ziwei; Zhou, Liyi; Lv, Tiantian; Wu, Fan; Liu, Zongxing; Zhao, Chang; Yu, Chunna; Xing, Guangjian
Abstract: The development of highly-selective absorbents with high separation flux for oil/water separation is a key requirement for wastewater pollution treatment. Herein, we successfully prepared a hydrophobic Ti3 C2 TX /polyurethane (Ti3 C2 TX /PU) sponge for oil/water separation with superior separation performance. The PU sponge selected in this paper features a sandwich-like structure with subcentimeter-level pores on its surface. After being modified with Ti3 C2 TX via a facile dip-coating process, the surface wettability of the PU sponge changed from amphiphilicity to hydrophobicity with a water contact angle of 122.4°. The as-prepared Ti3 C2 TX /PU sponge demonstrated high separation efficiencies (≥ 95.7%) and ultrahigh separation fluxes (up to 360340 L m −2 h −1 ) for various oil/water mixtures. Furthermore, it possessed a remarkable absorption capacity of 11–36 times its own weight towards a variety of oils and organic solvents. To verify the practical application of the Ti3 C2 TX /PU sponge, the separation and absorption performance was further investigated under various harsh conditions, such as high temperature, vigorous stirring, acidic/alkaline environments. Combining its excellent mechanical elasticity and recyclability, the Ti3 C2 TX /PU sponge can be suggested as a promising absorbent for removal of pollutants from wastewater under a wide range of harsh conditions. Graphical Abstract: ga1 Highlights: Hydrophobic Ti3 C2 TX /polyurethane (Ti3 C2 TX /PU) sponge was prepared successfully. Ti3 C2 TX /PU sponge exhibits high separation efficiencies for oil/water mixtures. Ti3 C2 TX /PU sponge shows ultrahigh separation fluxes (up to 360340 L m −2 h −1 ). Ti3 C2 TX /PU sponge shows high absorption capacities towards various oils/solvents.